Using virtual reality and head-mounted displays to increase performance in rowing workouts - Arndt, S.; Perkis, A.; Voigt-Antons, J.-N. (MMSports'18 Proceedings of the 1st International Workshop on Multimedia Content Analysis in Sports - Seoul, Republic of Korea — October 26 - 26, 2018, 2018)
Technology is advancing rapidly in the domain of virtual reality, as well as in using sensors to gather feedback from our body and the environment we are interacting in. Combining these two technologies gives us the opportunity to create personalized and reactive immersive environments. These environments can be used for training of dangerous situations (e.g. fire, crashes, etc) or to improve skills with less distraction than regular natural environments would offer. The pilot study described in this paper, puts an athlete rowing on a stationary rowing machine into a virtual environment. The virtual reality receives movement data from several sensors of the rowing machine and displays those in the head-mounted display. In addition, metrics on technique are derived from the sensor data as well as physiological data. All this is used to investigate if and to which extend VR improves the technical skills of an athlete, during the complex sport of rowing. Furthermore, athletes are given subjective feedback about their performance comparing the standard rowing workout with the workout using VR. First results indicate improved performance of the workout and an enhanced experience for the athlete in the VR condition.